Determinants of Company Value with Profitability as a Moderating Variable for Companies in the IDX ESG Leaders Index - Rohmah, Mufidatur; Sundari, Siti; Haryati, Tantina (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to test and analyze the determinants of company value with profitability as a moderator for companies in the IDX ESG Leaders Index for the 2019-2023 period. The sample in this research was 15 companies selected through purposive samplingwith 5 years of observations so the number of observations is 75. Data analysis techniques usingSEM-PLS is assisted by Smart-PLS 3.0 software. The results of this research show that agency costs have an effect on company value, while ESG disclosure and financial distress have no effect on company value in the IDX ESG Leaders Index. Apart from that, profitability is able to mediate the effect of ESG disclosure and agency costs on company value, but profitability is not able to mediate the effect of financial distress on company value in the IDX ESG Leaders Index.